Prototype Pagar Otomatis Berbasis Arduino Uno Dengan Sensor Ultrasonic Hc-SR04 - Imam Rama Muttaqin; Dian Budhi Santoso (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2021)
The process of opening and closing the fence manually is less effective, forexample, residents of the house have to go down and open the gate manually by pulling or pushing it by hand, whereas for certain conditions, such as when itrains, opening and closing the fence manually will make it difficult. . Thepurpose of this paper is to increase the efficiency and effectiveness of the gateopening and closing process, where the process of opening and closing the fence can be done practically by using a DC motor connected to an Arduino Uno and an ultrasonic sensor HC-SR04. The process of opening and closing the door will be faster because the driver does not need to push open the fence or close the fence.